The role of digital technologies in the public administration sphere: El papel de las tecnologías digitales en el ámbito de la administración pública - Popova, Liubov; Seniv, Bohdan; Korol, Volodymyr; Galushko, Oleksandr; Biriukov, Iegor (Political Questions, 2023)
The article is devoted to highlighting the role of digital technologies in the public administration sphere, taking into account the modern experience of the EU countries. The methodological basis of the research is the institutional approach, which provides for ensuring the effectiveness of the interaction between the components of the institutional system and the mechanisms of its implementation and control over the use of digital technologies and makes it possible to create an effective network of relationships between all levels of the system horizontally and vertically, as well as to increase the efficiency of the entire system public administration and the quality of public services. The advantages of the implementation of digital technologies in public administration are highlighted, which makes it possible to: increase the efficiency of public administration, reduce administrative costs, improve the quality of public services and ensure their availability, and reduce the level of corruption. The results of the implementation of digitalization of public services in the EU countries were analyzed in accordance with the program for the implementation of digital measures within the framework of the Recovery and Sustainability Fund. The necessary directions for the activation of the implementation of digital technologies in the public administration system are substantiated.